Cleanliness and Comfort Management of As-Sajdah Mosque as an Attraction for the Congregation - Asbiri; Nurlaili; Leny Marlina; Asri Karolina (al-Afkar, Journal For Islamic Studies, 2025)
This study aims to examine the management of cleanliness and comfort at As-Sajadah Mosque, Baturaja, and its impact on attracting the congregation. Employing a qualitative descriptive approach, this research analyzes the perceptions of mosque-goers regarding cleanliness and comfort, as well as other factors influencing their choice to worship at the mosque. Data collection was conducted through surveys, interviews, observations, and documentation involving both the congregation and mosque administrators. The findings reveal that effective cleanliness and comfort management significantly influence the congregation's willingness to visit and worship at the mosque. Key contributing factors include routine maintenance, the provision of adequate facilities, and efforts to raise awareness among the congregation about maintaining cleanliness. Additionally, the study highlights the strategic location of the mosque, appealing architectural design, well-maintained facilities, and community involvement in mosque activities as pivotal in enhancing its attractiveness. This study concludes that optimal mosque management plays a critical role in improving the quality of worship experiences and fostering a comfortable environment for the congregation. The results are expected to serve as a reference for mosque administrators seeking to implement effective cleanliness and comfort management practices.